Liver transplantation for homozygous familial hypercholesterolemia: a retrospective analysis from Chinese experience - Hao-Su Zhan; Lin Wei; Wei Qu; Zhi-Gui Zeng; Ying Liu; Yu-Le Tan; Jun Wang; Liang Zhang; En-Hui He; Guang-Peng Zhou; Hai-Ming Zhang; Zhi-Jun Zhu; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Homozygous familial hypercholesterolaemia (HoFH) increases risk of premature cardiovascular events and cardiac death. In severe cases of HoFH, clinical signs and symptoms cannot be controlled well by non-surgical treatments, liver transplantation (LT) currently represents the viable option. Method To assess the clinical efficacy, prognosis, and optimal timing of LT for HoFH, a retrospective analysis was conducted on the preoperative, surgical conditions, and postoperative follow-up of children who received an LT for HoFH at the Beijing Friendship Hospital over the period from December 2014 to August 2022. Results Xanthoma and decreased activity tolerance were the primary clinical manifestations in the 7 HoFH children initially assessed (one child died suddenly prior to surgery due to cardiac arrest). Accompanying these symptoms were increased blood total cholesterol (TC) and low density lipoprotein (LDL) levels, along with severe cardiovascular diseases. HoFH was confirmed in all cases by genetic and biochemical assays. Initial treatments administered to these patients consisted of low-fat diets and lipid-lowering drugs with poor outcomes. Accordingly, all 6 patients received orthotopic liver transplantations (OLT), with the result that significant postoperative reductions were observed in levels of TC and LDL. The median follow-up of these six cases was 37.41 months (range: 19.40–94.10 months). Regular postoperative follow-ups revealed that all survived and showed significant improvements in their clinical symptoms. Conclusion So far, LT is the only way to heal HoFH. LT before the appearance of obvious cardiovascular atherosclerotic lesions can significantly improve the quality of life and prognosis of patients. At the same time, the blood cholesterol level of patients should be continuously monitored after LT to further control the progression of vascular complications.